Penataan Desa Adat di Kota Ambon (Legitimasi Status Negeri Secara Nasional) - Lainsamputty, Natanel; Soplantila, Ronny; Nirahua, Graciano (Jurnal Saniri, 2023)
Ambon City is the capital city in Maluku Province which has a customary law community unit called the Country, in the Village Law regulations it is obligatory to organize villages into traditional villages and villages. Determination of State in Ambon City with Regional Regulation No. 9 of 2017, if viewed from the applicable laws and regulations, the determination is not in accordance with the applicable regulations, where there must be legitimacy through the code or the Traditional Village Register Number. According to the procedure, before the determination of customary villages and villages is carried out, it is necessary to determine the recognition and protection of customary law communities, because that is a requirement for being designated as a traditional village. The research method used in this paper is normative research with a statutory approach as data primary as well as by using concepts, theories as library materials which are secondary data to analyze the issue of determining the Traditional Village in Ambon City. The results of this study indicate that until now the status of the State in Ambon City is still unclear and must be adjusted to the applicable regulations.